DEVELOPMENT OF ENGLISH POP-UP BOOK MEDIA TO TEACH WRITING SKILL AT JUNIOR HIGH SCHOOL - Aida Nur Ita; Siti Rofi'ah; Istina Atul Makrifah (Universitas Wiralodra, 2024)
This study aims to ensure that the use of Pop-Up Book Media affects the writing abilities of junior high school students. This media focuses with Descriptive Text material to teach writing skill to class VII students. This research use ADDIE model. The sample for this research was class VIIA MTs Sunan Ampel Kediri, totaling 14 students. Data collection was carried out by observation, unstructured interviews with teacher and questionnaires. Data were analyzed using a manual percentage formula. These findings show that the validation percentage of media experts reached 98%, that means